Efficient Market Hypothesis and Forecasting of the Industrial Sector on the Indonesia Stock Exchange - Faizul Mubarok; Mohammad Masykur Fadhli (Journal of Economics, Business, and Accountancy Ventura, 2020)
The presence of the stock market has helped boost economic growth in Indonesia. However, high levels of volatility plus economic uncertainty make investors need to carry out strategies in investing in the capital market. This study aims to analyze the index movement of each industry sector on the stock exchange in Indonesia by testing the Efficient Market Hypothesis and estimating the growth of returns for each industrial sector. This research uses monthly data from 1996 to 2020 with research methods including variance ratios, data stationarity test, Autoregressive Integrated Moving Average (ARIMA), and Autoregressive Conditional Heteroskedasticity (ARCH). The results showed that the industrial sector on the Indonesia Stock Exchange was inefficient in its weak form. In forecasting, almost all indices experience a contraction of growth at the beginning of the forecasting period. Stakeholders are expected to be more active in the market by buying and selling, especially the contraction of shares. The market has proven to be inefficient in its weak form.